2019
DOI: 10.1080/10580530.2020.1696526
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Speed on Customer Satisfaction and Switching Intention: A Study of the UK Mobile Telecom Market

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
6
9
0
Order By: Relevance
“…A speedy internet at affordable rates is expected by customers. Our this finding is in congruence with the findings of Dey et al ( 2020 ), who conducted a study in the UK telecom market and concluded that speed is an important factor that influences customer satisfaction and churning intention. The scale of international calls is increasing day by day due to globalization so the charges also need to be reasonable and competitive so that customers can make international calls at affordable prices.…”
Section: Findings and Conclusionsupporting
confidence: 92%
“…A speedy internet at affordable rates is expected by customers. Our this finding is in congruence with the findings of Dey et al ( 2020 ), who conducted a study in the UK telecom market and concluded that speed is an important factor that influences customer satisfaction and churning intention. The scale of international calls is increasing day by day due to globalization so the charges also need to be reasonable and competitive so that customers can make international calls at affordable prices.…”
Section: Findings and Conclusionsupporting
confidence: 92%
“…Lastly, this study also contributes methodologically, unlike previous studies which have applied SEM (Albashrawi & Motiwalla, 2020; Chang et al, 2020; Dey et al, 2020), which could only detect linear associations among the constructs. This study has gone a step ahead by applying the Artificial Intelligence tool ANN with deep architecture to cover the existing lacunas, that is, detecting both linear and non-linear associations among the studied variables.…”
Section: Implicationmentioning
confidence: 97%
“…Saleem et al (2018) argued whether consumers are satisfied with the products or services quality provided by the company and establishing a good BI will be the focus of business operations. Dey et al (2020) contended service quality positively affect corporate image; the better the service quality, the better the brand image. de Ruyter and Wetzels (2000) pointed out that in terms of corporate credibility and expected service quality, consumer service expansion is more favorable for providers with the image of innovative latecomers than for companies with brand image.…”
Section: Perceived Service Quality and Brand Imagementioning
confidence: 99%